Excitation of baryonic resonances in stable medium-mass nuclei of Sn. (October 2020) - Rodríguez-Sánchez, J L; Benlliure, J; Haettner, E; Scheidenberger, C; Vargas, J; Ayyad, Y; Alvarez-Pol, H; Atkinson, J; Aumann, T; Beceiro-Novo, S; Boretzky, K; Caamaño, M; et al.
Abstract: Isobaric charge-exchange reactions induced by beams of 112 Sn have been investigated at the GSI facilities using the fragment separator FRS. The high-resolving power of this spectrometer makes it possible to obtain the isobaric charge-exchange cross sections with an accuracy of 3% and to separate quasi-elastic and inelastic contributions in the missing-energy spectra, in which the inelastic component is associated to the in-medium excitation of baryonic resonances such as the Δ resonance. We report on the results obtained for the (p, n) and ( n, p ) channels excited by using different targets that cover a large range in neutron excess.